Changes in failure to rescue after gastrectomy at a large-volume center with a 16-year experience in Korea - Sung Hyun Park; Ki-Yoon Kim; Minah Cho; Yoo Min Kim; Woo Jin Hyung; Hyoung-Il Kim (Scientific Reports, 2023)
Abstract Failure to rescue (FTR), the mortality rate among patients with complications, is gaining attention as a hospital quality indicator. However, comprehensive investigation into FTR has rarely been conducted after radical gastrectomy for gastric cancer patients. This study aimed to assess FTR after radical gastrectomy and investigate the associations between FTR and clinicopathologic factors, operative features, and complication types. From 2006 to 2021, 16,851 gastric cancer patients who underwent gastrectomy were retrospectively analyzed. The incidence and risk factors were analyzed for complications, mortality, and FTR. Seventy-six patients had postoperative mortality among 15,984 patients after exclusion. The overall morbidity rate was 10.49% (1676/15,984 = 10.49%), and the FTR rate was 4.53% (76/1676). Risk factor analysis revealed that older age (reference: < 60; vs. 60–79, adjusted odds ratio [OR] 2.07, 95% confidence interval [CI] 1.13–3.79, P = 0.019; vs. ≥ 80, OR 3.74, 95% CI 1.57–8.91, P = 0.003), high ASA score (vs. 1 or 2, OR 2.79, 95% CI 1.59–4.91, P < 0.001), and serosa exposure in pathologic T stage (vs. T1, OR 2.74, 95% CI 1.51–4.97, P < 0.001) were associated with FTR. Moreover, patients who underwent gastrectomy during 2016–2021 were less likely to die when complications occurred than patients who received the surgery in 2006–2010 (OR 0.35, 95% CI 0.18–0.68, P = 0.002). This investigation of FTR after gastrectomy demonstrated that the risk factors for FTR were old age, high ASA score, serosa exposure, and operation period. FTR varied according to the complication types and the period, even in the same institution.